The association between obstructive sleep apnoea and diabetic peripheral neuropathy in subjects with type 2 diabetes - Lu, Na; Cheng, Gang; Qian, Yu; An, Di; Yin, Fuzai; Hou, Yajing; Liu, Xiaoli; Lu, Qiang; Ma, Chunming; Wang, Rui (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to examine the association between obstructive sleep apnoea (OSA) and diabetic peripheral neuropathy (DPN) in subjects with type 2 diabetes mellitus (T2DM).MethodsA cross-sectional study was conducted involving 228 T2DM subjects at The First Hospital of Qinhuangdao. OSA was assessed using polysomnography. DPN was diagnosed based on clinical signs, symptoms and electromyography findings. Small fibre neuropathy was additionally assessed through corneal confocal microscopy. Among these T2DM subjects, 124 (54.4%) had DPN. The prevalence of OSA was 67.5% (mild OSA 30.7%, moderate-to-severe OSA 36.8%). DPN prevalence rates were 40.5%, 52.9% and 67.9% in subjects without OSA, with mild OSA, and with moderate-to-severe OSA respectively. Multiple logistic regression analysis revealed that moderate-to-severe OSA was independently associated with DPN in T2DM subjects (AOR=2.176, 95%CI:1.050-4.511, p=0.037). Multiple linear regression analysis demonstrated that apnea hypopnea index (AHI) was independently associated with corneal nerve fiber length (CNFL)(coefficient=-0.032, p=0.049, R2 = 0.029) and CNFT (coefficient=0.023, p<0.001, R2 = 0.171) in T2DM subjects.ConclusionT2DM subjects with OSA demonstrate significantly higher odds of DPN. Furthermore, OSA shows a significant correlation with small fibre damage in T2DM subjects.